Finding of Blastocystis sp. in bivalves of the genus Donax - Pérez-Cordón, Gregorio (2007)
Although commonly detected in humans, microorganisms identified as Blastocystis have also been isolated from a wide range of animals, such as primates, pigs, cattle, birds, amphibians and, less frequently, rodents and insects. In the present paper, we describe the detection of Blastocystis sp. in bivalve mollusks of the genus Donax from the Peruvian northern coast. This finding extends the host range of this pathogen, opening the possibility of Blastocytis transmission to human beings by marine mollusks.